The Role of the Election Supervisory Agency for West Halmahera Regency in Resolving Law Violations at the Election and Vote Count Stages in the 2019 Election - Bambang Daud; Yahya Yunus (Khairun Law Journal, 2021)
The problems in this research consist of: What are the forms of violations that occur at the voting & counting stages in the 2019 simultaneous general election in West Halmahera Regency What is the role of Bawaslu Halbar in resolving violations that occur during the holding of general elections simultaneously year 2019 in the West Halmahera Regency area.The location of field research was carried out in West Halmahera district. The type of normative-empirical research uses a statute approach and a conceptual approach. Types and sources of data are primary legal data and secondary legal data. Data collection techniques are carried out. by interviewing and documenting the data for further qualitative analysis.The purpose of this research is to conduct a study and analysis to find out what forms of violations that occur at the voting and counting stages in the 2019 simultaneous general elections in the West Halmahera Regency area. To find out how to resolve violations that occur during the holding of general elections simultaneously in 2019 in the West Halmahera Regency area.Whereas the forms of violations handled by Bawaslu Halbar in dealing with founding violations totaled 11 (eleven) election violations, and in handling only 3 (three) election violations recommended by the Integrated Law Enforcement Center. Besides that, 1 (one) finding that has been decided has permanent legal force. Meanwhile, other findings were not continued because the elements of election violations were not fulfilled based on the results of the study of alleged violations. The forms of violations are as follows: (1) Election Crime, there are 10 (ten) cases of criminal violations handled by Bawaslu Halbar. However, the handling process can be forwarded to the Police for only 3 (three) cases based on the results of the Bawaslu Halbar study; and (2) Violation of Liannya's Law, namely the findings of Muhammadun Hi's alleged violation of ASN neutrality. Adam on April 6, 2019 and has been registered with number 03 / TM / PL / KAB / 32.03 / IV / 2019. Based on the results of Bawaslu Halbar's study, the findings of the alleged violation of ASN Neutrality were given a recommendation to be sanctioned by the State Civil Apparatus Commission (KASN). As for the form of Election administration violations, Bawaslu Halbar did not receive reports or findings during the 2019 simultaneous elections. In addition, in terms of violations of the code of ethics, Bawaslu Halbar did not find any violations of the code of ethics committed by Election Administrators in the West Halmahera Regency either by election organizers. still namely the Election Commission of West Halmahera Regency and the organizer of the Ad Hoc Election.That Bawaslu Halbar has carried out its role as a supervisory agency for the implementation of the 2019 simultaneous elections very well. This can be seen from the actions of Bawaslu Halbar in handling violations both in the form of findings and reports of general election violations. Bawaslu Halbar handles findings of alleged violations according to working days or from the day the public finds out about and / or reports the alleged violation. Then the results are reported or stated in form B-1 and .discussed in the Plenary Meeting of the Follow-up of Initial Information on Alleged Violations to determine whether or not there are allegations of election violations, and if the election supervisor states that there is a violation of the general election, the election supervisor determines to be registered or recorded in Election register book. Bawaslu Halbar handles reporting violations totaling 8 (eight) election violations, and in handling only 1 (one) election violation that fulfills the formal and material elements. Meanwhile 2 (two) Election Violation Reports will be withdrawn by the Reporting Party. Other reports cannot be followed up because the violation elements and / or material elements are not fulfilled based on the results of the plenary meeting to follow up the initial information on the alleged violation. During the process, the election stages took place starting from the data updating stage and the recapitulation plenary session at each level, 8 (eight) reports of alleged violations from the public were received and 2 (two) of them were withdrawn by the reporter. reports that have been registered cannot meet sufficient evidence so that they are terminated, while 1 (one) other report has been reviewed and recommended to the Integrated Law Enforcement Center (Gakumdu) or related agencies because it fulfills the elements of an election criminal offense.